Gender integration in Local Water Resource Governance Institutions: A case of Community Owned Water Supply Organisations (COWSOs) in Gairo District, Tanzania - Haule, Ambonisye; Massawe, Fatihiya Ally (IJRDO - Journal of Social Science and Humanities Research, 2020)
Given the growing demand for water resources and its continue scarcity efforts have been in place to change governance mechanisms to ensure its sustainability. The sector transformation focuses on enhancing user’s capacity in developing, managing and sharing water resources efficiently. Women are among the actors that are now recognized as managers than mere users of water resources given their gender roles. Therefore, policies and water resource management strategies in many countries including Tanzania, demand women involvement in Community Owned Water Supply Organizations (COWSOs). The argument of this paper is that call for women representation in water governance structures might not necessarily transform gender relations among men and women hence making women voices unheard. Therefore, this study presents gender dynamics in COWSOs in various villages of Gairo District, Tanzania by exploring power and leadership positions held by men and women. The findings show that under the support of external actors, women are holding a various leadership position in COWSOs though the strategic power of making decisions are still held by men. The study concludes that numbers are not enough without capacity building for women to be able to influence decision making.